Identification of an antivirulence agent targeting the master regulator of virulence genes in Staphylococcus aureus - Arya, Rekha; Kim, Truc; Youn, Joo Won; Bae, Taeok; Kim, Kyeong Kyu (Frontiers in Cellular and Infection Microbiology, 2023)
The emergence of bactericidal antibiotic-resistant strains has increased the demand for alternative therapeutic agents, such as antivirulence agents targeting the virulence regulators of pathogens. Staphylococcus aureus exoprotein expression (sae) locus, the master regulator of virulence gene expression in multiple drug-resistant S. aureus, is a promising therapeutic target. In this study, we screened a small-molecule library using a SaeRS green fluorescent protein (GFP)-reporter that responded to transcription controlled by the sae locus. We identified the compound, N-(2-methylcyclohexyl)-11-oxo-10,11-dihydrodibenzo[b,f][1,4]thiazepine-8-carboxamide (SKKUCS), as an efficient repressor of sae-regulated GFP activity. SKKUCS inhibited hemolysin production and reduced α-hemolysin-mediated cell lysis. Moreover, SKKUCS substantially reduced the expression levels of various virulence genes controlled by the master regulators, sae, and the accessory gene regulator (agr), demonstrating its potential as an antivirulence reagent targeting the key virulence regulators. Furthermore, autokinase inhibition assay and molecular docking suggest that SKKUCS inhibits the kinase activity of SaeS and potentially targets the active site of SaeS kinase, possibly inhibiting ATP binding. Next, we evaluated the efficacy and toxicity of SKKUCS in vivo using murine models of staphylococcal intraperitoneal and skin infections. Treatment with SKKUCS markedly increased animal survival and significantly decreased the bacterial burden in organs and skin lesion sizes. These findings highlight SKKUCS as a potential antivirulence drug for drug-resistant staphylococcal infections.